Preparation and Characterization of Calcium Carbonate Reinforced Poly (3-hydroxybutyrate-co-3-hydroxyvalerate) Biocomposites - Kirboga, Semra; Oner, Mualla; Deveci, Suleyman (BENTHAM SCIENCE PUBL LTD, 2021)
Background: The objective of this work was to develop biopolymer/calcium carbonate biocomposites with enhanced properties, relative to the neat polymer, by using low-cost filler calcium carbonate (CaCO3). To this end, we selected as matrices Poly (3-hydroxybutyrate-co-3-hydroxyvalerate, PHBV), which has attracted the most considerable interest among the biopolymers in industry. Methods: Novel biodegradable PHBV/CaCO3 composites with 0.1-1 wt% of CaCO3 content were manufactured by melt extrusion. The effect of the CaCO3 on the thermal, barrier and dynamic mechanical properties of the PHBV was comprehensively investigated by SEM, XRD, FTIR, TGA, DSC, and DMA. The water and oxygen barrier properties of the biocomposites were also measured. Results: DSC and XRD analysis showed that CaCO3 served as a nucleating agent, promoting crystallinity and crystal size. The addition of CaCO3 particles has a small effect on lamellae thickness and distribution. DMA measurements showed considerable improvements in storage modulus and viscose damping by incorporating CaCO3 particles. The storage modulus of the PHBV at 20 degrees C in the DMA was increased up to 76% and loss modulus was increased up to 175% when composite was prepared with 0.1wt% coated CaCO3 particle. Water vapor and oxygen permeability were measured to study the effect of particles on the barrier properties of composite samples. Biocomposites exhibited smaller oxygen transmission rate (OTR) and water vapor transmission rate (WVTR) due to the increase in crystallinity and tortuosity of the composite samples. Conclusion: The results of this study have demonstrated that properties of biocomposites prepared by using low-cost commercially available filler are greatly improved to obtain high-performance composites.
Keywords: Green polymer; biocomposite; PHBV; calcium carbonate; thermal and barrier properties; DSC and XRD analysis; Biotechnology & Applied Microbiology; Science & Technology - Other Topics; Materials Science